2007
DOI: 10.1007/s00125-007-0859-x
|View full text |Cite
|
Sign up to set email alerts
|

Oral taurine but not N-acetylcysteine ameliorates NEFA-induced impairment in insulin sensitivity and beta cell function in obese and overweight, non-diabetic men

Abstract: Aims/hypothesis Antioxidants have been shown to ameliorate lipid-induced impairment of insulin action and beta cell function, both in vitro and in animal studies. The aim of the present study was to examine the effects of two orally administered antioxidants, N-acetylcysteine (NAC) and taurine (TAU), on lipotoxicity in humans. Methods Nine non-diabetic men, who were either overweight or obese, underwent three studies each, 4-6 weeks apart, in random order: (1) i.v. infusion of saline for 48 h (SAL); (2) i.v. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 44 publications
2
69
0
3
Order By: Relevance
“…Our collaborative studies in humans (Xiao et al 2008) show that oral taurine prevents wholebody insulin resistance caused by prolonged (48 h) IH infusion and this is accompanied by a reduction in the plasma levels of markers of oxidative stress, namely MDA and 4-hydroxynonenal. In contrast, oral NAC was not effective at improving insulin sensitivity, likely as a result of NAC being metabolized by the liver due to its route of administration (Xiao et al 2008). These studies, however, did not distinguish the role of oxidative stress in individual tissues in FFA-induced insulin resistance.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our collaborative studies in humans (Xiao et al 2008) show that oral taurine prevents wholebody insulin resistance caused by prolonged (48 h) IH infusion and this is accompanied by a reduction in the plasma levels of markers of oxidative stress, namely MDA and 4-hydroxynonenal. In contrast, oral NAC was not effective at improving insulin sensitivity, likely as a result of NAC being metabolized by the liver due to its route of administration (Xiao et al 2008). These studies, however, did not distinguish the role of oxidative stress in individual tissues in FFA-induced insulin resistance.…”
Section: Discussionmentioning
confidence: 86%
“…Obesity is associated with elevated circulating free fatty acids (FFAs) and FFAs cause insulin resistance (Lewis et al 2002, Xiao et al 2008. FFAs induce oxidative stress (Nakamura et al 2009, Yuzefovych et al 2010, Gurzov et al 2014, which occurs when the rate of reactive oxygen species (ROS) production is greater than their removal (Evans et al 2002), and ROS cause insulin resistance (Hansen et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is associated with elevated circulating free fatty acids (FFAs) (17), which induce oxidative stress by promoting the production of reactive oxygen species (ROS) to a level greater than their removal, and the high level of ROS is the main cause of insulin resistance (18,19). A high-fat diet is associated with a reduction in the hepatic levels of the antioxidant glutathione (GSH) and diminished activity of antioxidant enzymes, while the activity of some enzymes such as NADPH oxidase which produce ROS, is augmented (20,21).…”
Section: Pathogenesismentioning
confidence: 99%
“…Because the main effects of hyperlipidemia seem to occur in the adipose tissue, it seems plausible to assume that, if adipose tissue insulin sensitivity had been measured separately, a difference in the insulin sensitivity between lipidinfused and saline-infused cats would have been detectable seems justifiable. Different from the result in cats, former studies in humans and rodents consistently showed an impairment of whole body insulin sensitivity following lipid infusion [30][31][32][33][34][35]. Hence, it may be argued that the effect of hyperlipidemia on insulin sensitivity differs between cats and humans and rodents.…”
Section: Discussionmentioning
confidence: 77%